2015
DOI: 10.1002/admi.201500352
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Anti‐Icing Abilities of Optimal Micropillar Arrays with Nanohairs

Abstract: of adhesion required to remove a liquid water drop. Poulikakos and co-workers [ 7 ] investigated surfaces with nanometerscale roughness and higher wettability, which display long freezing delays, one order of magnitude longer than typical superhydrophobic surfaces with larger hierarchical roughness and low wettability. And Poulikakos also established [ 8 ] that evaporative cooling of the supercooled liquid could engender ice crystallization by homogeneous nucleation at the droplet-free surface as opposed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 34 publications
(33 reference statements)
1
29
0
Order By: Relevance
“…Following hydrophobization with heptadecafluorodecyltripropoxysilane (FAS-17), water drops remained in a non-freezable state at -5°C and rolled off the surface when exposed to breeze, due to the water-repellent properties of the surface (WCA ≈ 150°). Epoxy micropillars arrays covered with ZnO nanohairs fabricated by soft replication methods ("Bosch process") and crystalgrowth techniques have shown better results in terms of ice formation delay [102]. In this case, an icing delay time as high as 9839 s was noticed in the FAS-treated surfaces (an icing delay time of 7360 s at -10°C was reported in the previous study), even though the contact angle was virtually the same (WCA ≈ 152°) (Fig.…”
Section: Lithographysupporting
confidence: 51%
See 1 more Smart Citation
“…Following hydrophobization with heptadecafluorodecyltripropoxysilane (FAS-17), water drops remained in a non-freezable state at -5°C and rolled off the surface when exposed to breeze, due to the water-repellent properties of the surface (WCA ≈ 150°). Epoxy micropillars arrays covered with ZnO nanohairs fabricated by soft replication methods ("Bosch process") and crystalgrowth techniques have shown better results in terms of ice formation delay [102]. In this case, an icing delay time as high as 9839 s was noticed in the FAS-treated surfaces (an icing delay time of 7360 s at -10°C was reported in the previous study), even though the contact angle was virtually the same (WCA ≈ 152°) (Fig.…”
Section: Lithographysupporting
confidence: 51%
“…The "two-step" route (Fig. 6a), which is typically applied to ceramic substrates, is based on the deposition of "building units" followed by a treatment with a low surface energy material [99][100][101][102][103], while the "three-step" route (Fig. 6b) consists of surface microstructuring of a polymeric substrate by soft lithography (section 4.2.2), followed by coating deposition and hydrophobization [104,105].…”
Section: How To Prevent Surfaces From Fogging Up: Anti-fogging Strategies Mechanisms and Materialsmentioning
confidence: 99%
“…Compared with a traditional, textured superhydrophobic surface, water strider legs exhibit a robust water repellency that could be used on a femtoliter scale, and the legs could inspire the design of novel superhydrophobic materials for practical applications, such as antidew and anti-icing materials and dropwise condensers. [19] Recently, Quéré and co-workers compared the water condensation behaviors of nanopillars (Sample A) and nanocones (Sample C) (Figure 3a 4 ) and demonstrated that the conical shape of a nanostructure is crucial for further enhancing its antifogging ability. [20] The conical geometry provides a Laplace expulsion out of the texture, prevents the formation of durable wet patches, maintains the liquid in a full Cassie state, even for isolated microdrops (Figure 3a 5 ).…”
Section: Water Strider Leg: Self-removal Of Condensed Dropletsmentioning
confidence: 99%
“…Nanostructures on a microstructured surface (hereafter referred to simply as a micro–nanostructure) are gaining increased attention for their potential applications in the fields of anti‐icing [1, 2], superhydrophobic materials [3], drag reduction [4], oil–water separation [5], biochemical sensors [6], bionics [7], medical science [8], optics [9] and so on.…”
Section: Introductionmentioning
confidence: 99%